2011
DOI: 10.1124/mol.111.073874
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone and Metformin Have Opposite Effects on Intestinal Absorption of Oligopeptides via the Proton-Dependent PepT1 Transporter

Abstract: The intestinal H(ϩ)/peptide cotransporter 1 (PepT1) plays a major role in nitrogen supply to the body by mediating intestinal absorption of di-and tripeptides. Previous studies have reported that in animal models of type 2 diabetes/obesity, PepT1 activity and expression were markedly reduced. This prompted us to investigate the effects of two antidiabetic drugs, rosiglitazone and metformin, on PepT1 activity/expression in a murine diet-induced obesity model. C57BL/6J male mice were fed a high-fat diet (HFD) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…With regards to PEPT1, a previous study reported that mice fed an HFD exhibited reduced [ 3 H] Gly-Sar transport, reflecting low PEPT1 activity [32]. Indeed, it is plausible that this observed decrease in activity could be the consequence of the diminished PEPT1 content observed in the mice fed an HFD.…”
Section: Discussionmentioning
confidence: 96%
“…With regards to PEPT1, a previous study reported that mice fed an HFD exhibited reduced [ 3 H] Gly-Sar transport, reflecting low PEPT1 activity [32]. Indeed, it is plausible that this observed decrease in activity could be the consequence of the diminished PEPT1 content observed in the mice fed an HFD.…”
Section: Discussionmentioning
confidence: 96%
“…This dose of oral rosiglitazone (estimated at 8 mg/kg/day) was previously shown by our laboratory to significantly suppress chemical carcinogenesis in mice [41] and to block ultraviolet B-induced immune suppression [1]. Similarly, this dose is within the range of doses that have pharmacologic activity in mice [44,45]. C57BL/6J or NOD SCID mice were then injected intradermally with either 1 × 10 6 or 5 × 10 6 PDV tumor cells.…”
Section: Methodsmentioning
confidence: 99%
“…The estimated daily intake was 8 mg/kg/day. Oral rosiglitazone has been shown to be systemically active in mice at doses of 3-8 mg/kg/day [ 58 , 59 ]. An approximately 2.5 × 2.5-cm area of the distal back skin of these mice were treated with 7500 J/m 2 UVB or were left untreated.…”
Section: Methodsmentioning
confidence: 99%